Peran Unit Dikyasa Dalam Mengurangi Angka Kecelakaan Lalulintas Melalui Program Safety Riding Terhadap Pelajar SMA Di Wilayah Hukum Polrestabes Bandung - Ihsan Hamami (Police Studies Review, 2020)
Public transportation in Bandung has a long route and plays and takes a lot of time. This has caused many students to switch from public transportation to private vehicles such as motorbikes. The high number of students who use private vehicles without following self-awareness in an orderly traffic often leads to traffic accidents. The number of traffic accidents committed by students is the responsibility of the Dikyasa Unit. To overcome this the Bandung Polrestabes Dikyasa Unit provides Dikmas Lantas through the Safety Riding program. This research uses a qualitative approach with interviews to explore deeper facts. Resource persons in this study were selected by researchers based on certain considerations. Theories and concepts used by researchers are management theory, the concept of Safety Riding, the Dikmas Lantas concept, and the Student concept. The research findings show that traffic accidents by students in the city of Bandung are the result of lack of awareness from within the student, the influence of association, long distance to school, as well as the indifference of parents. But in its implementation the activity has not been carried out as it should and is not optimal. Factors that influence the implementation of the Safety Riding program carried out by the Bandung Polrestabes Dikyasa Unit in accordance with the theory of management elements, that these factors are divided into two namely internal and external factors. The internal factors include: the minimum number of peronil, the density of Dikyasa unit activities, inadequate budget. The positive factors or those that can support include: a high willingness to learn personnel, and Dikyasa units have a good strategy. External factors that can affect activities include: Lack of demand from schools, and students who do not fully support activities.